PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU BERPRESTASI DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) (Studi Kasus: SMA INFORMATIKA CIAMIS) - Rohayati, Tuti; Maulana, Haisyam; Juwita Sari, Deassy Ratna (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
This research discusses the design of a decision support system for selecting outstanding students using the simple addictive weighting (saw) method in a case study at SMA Informatika Ciamis. The purpose of this research is to facilitate the assessment of outstanding teachers, it is necessary to create a system that is able to provide maximum results and can facilitate the process of selecting outstanding teachers in terms of assessment, data processing and data input. This study uses several relevant theories such as Decision Support Systems. The research method used in this research is the SAW method, the Simple Additive Weighting (SAW) method. In Ciamis Informatics High School as one of the largest private high schools in Ciamis every year an election for outstanding teachers is always held. From previous experience, every selection of outstanding teachers always had problems, including the lack of attention to the weight of the assessment of each of the criteria for evaluating outstanding teachers. The weight of the assessment includes attendance, discipline, professionalism, personality and social.